(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract : This research demonstrates the importance of banking technology in enhancing the strategic ability to achieve serious knowledge work in economic growth by identifying the role of banking technology represented by (hardware components, software, communication networks, human resources, database) in enhancing the strategic ability in a sample of private commercial banks. In the city of Baghdad . In the theoretical aspect of the research, the researcher addressed the research problem of what is the impact of banking technology in enhancing strategic capabilities. The research hypothesis was formulated: Can banking technology be used to enhance strategic? capabilities? Is there a relationship between banking technology and strategic ability . To achieve this goal, the researcher prepared a questionnaire and the researcher reached a set of conclusions, the most important of which are: The results showed that banking technology has an effective role in enhancing the strategic ability to develop and support aspects of economic activity, and that workers in the banking system possess high skills and experience using modern and different technologies and software in providing banking services with efficiency and quality High.